Electoral Governance and Democratic Vulnerability Amid Disaster in the 2024 East Flores Regional Election - Eusabius Separera Niron; Yonatan Hans Luter Lopo (JOURNAL OF GOVERNMENT SCIENCE, 2026)
Previous studies generally examine the implementation of elections in crisis situations from a logistical and administrative perspective, while attention to the interactions between election governance, disaster governance, and democratic vulnerability is still relatively limited. To fill this gap, this study investigates how election governance was implemented during the Mount Lewotobi eruption and how these conditions shaped democratic vulnerabilities in the 2024 East Flores Regency Regional Head Election. This research offers a novel contribution by integrating the perspectives of election governance and democratic vulnerability in a disaster context. Using a qualitative case study approach, data were collected through interviews with 15 key informants, document analysis, and field observations. They were then analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and conclusion drawing. The results show that disaster conditions not only disrupt election administration but also create democratic vulnerabilities related to voter access, political representation, and election legitimacy. This research contributes to the development of literature on the implementation of regional elections in an emergency context and recommends the development of a disaster-responsive regional election governance framework to strengthen democratic resilience in future regional elections.